In defense of “sex education”: meanings produced in videos by youtuber Felipe Neto - Priscila Gonçalves dos Santos, Michele (2023)
The article aims to present part of the analyzes of a master's research in education, focusing on the discourses of gender and sexuality that circulate in videos by the youtuber Felipe Neto on his YouTube channel. Videos were selected, based on the platform's own search mechanisms, in which the influencer triggers statements that refer to various issues involving gender and sexuality. The theoretical-methodological perspectives that led the investigation are aligned with the discourse analysis inspired by Foucault and post-structuralist theories. The article mobilizes arguments from the videos in which the youtuber assumes certain positions about what he calls “sex education”. Our analyzes lead us to problematize the relationship between the videos and the contemporary conservative context, promoting enunciative disputes around the idea of informing young people about sexuality issues.